1983
DOI: 10.1002/ar.1092050305
|View full text |Cite
|
Sign up to set email alerts
|

Light and scanning electron microscopic study of testosterone‐restored penile papillae in castrated rats

Abstract: Structural changes in various penile tissue from rats with differing circulating androgen levels were analyzed with light and scanning electron microscopy. Adult males were castrated and daily injected for 6 weeks with one of four physiologic amounts of testosterone propionate (TP). Results indicated that epithelium, subepithelial connective tissue, and the papillae protruding from the surface of the glans penis responded, more or less, in a dose-dependent fashion to the steroid. The least androgen-sensitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…There have been reports of several species that develop penile spines in their external genitalia (Taylor et al ., 1983;Murakami, 1987). Penile spines develop by an androgen dependent manner (Whitsett et al ., 1980;Ninomiya et al ., 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports of several species that develop penile spines in their external genitalia (Taylor et al ., 1983;Murakami, 1987). Penile spines develop by an androgen dependent manner (Whitsett et al ., 1980;Ninomiya et al ., 1984).…”
Section: Discussionmentioning
confidence: 99%
“…While ovulation in mice and rats is considered as spontaneous, the penile spines are speculated to play some roles in inducing ovulation in such species. Thus, their development may not simply enable species with spontaneous ovulation to be distinguished from species with post-coital ovulation (Taylor et al ., 1983;Murakami, 1987;Bedford et al ., 1997). It is also reported that penile spines may play some roles in efficient erection and ejaculation for copulation (Dixson, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…As is likely apparent, the study just described illustrates another important issue in hormone research: dosing. Future studies on the behavioral effects of hormone supplements may benefit from using multiple levels of exposure rather than using the one we have found useful in our lab [21]. …”
Section: Resultsmentioning
confidence: 99%
“…Males were subcutaneously injected with either 4-A, DHEA, TS, CORT or oil only (vehicle). Hormones were administered as 400 µg steroid/kg of body weight (bwt) [21]. Estradiol benzoate (100 µg/kg bwt) and progesterone (400 µg/kg bwt) were used to induce behavioral estrus in ovariectomized females [27].…”
Section: Methodsmentioning
confidence: 99%
“…The accessory sex glands are stimulated to grow (Hunt, 1968) and their secretory activities are increased (Agmo, 1974). Penile morphology is modified as the papillae on the surface of the glans become uniformly large in response to increased levels of circulating hormone (Taylor, Komitowski & Weiss, 1983a;Taylor, Weiss & Komitowski, 1983c).…”
Section: Introductionmentioning
confidence: 99%